2017
DOI: 10.1038/nmicrobiol.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PfEMP1–VAR2CSA translation by a Plasmodium translation-enhancing factor

Abstract: Pregnancy-associated malaria commonly involves the binding of Plasmodium falciparum-infected erythrocytes to placental chondroitin sulfate A (CSA) through the PfEMP1-VAR2CSA protein. VAR2CSA is translationally repressed by an upstream open reading frame. In this study, we report that the P. falciparum translation enhancing factor (PTEF) relieves upstream open reading frame repression and thereby facilitates VAR2CSA translation. VAR2CSA protein levels in var2csa-transcribing parasites are dependent on the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…CSs are known to be involved in cancer metastasis [1] , parasitic infections [2] and neuron growth inhibition after injury [3] . The sulfation patterns in CS dictate the binding affinity to the protein targets to manifest the selectivity in biological functions [4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CSs are known to be involved in cancer metastasis [1] , parasitic infections [2] and neuron growth inhibition after injury [3] . The sulfation patterns in CS dictate the binding affinity to the protein targets to manifest the selectivity in biological functions [4] .…”
mentioning
confidence: 99%
“…The sulfation patterns in CS dictate the binding affinity to the protein targets to manifest the selectivity in biological functions [4] . A 6- O -sulfated N -acetyl galactosamine (GalNAc6S) containing CS facilitates the infection of B. burgdorferi to cause lyme disease [5] , and 4- O -sulfated N -acetyl galactosamine (GalNAc4S) involves in P. falciparum infection that causes malaria [2a] . A domain containing 4,6 disulfated N -acetyl galactosamine (GalNAc4S6S) residues is proved to be necessary to direct neuronal signaling and inhibit axon growth [3c, 6] .…”
mentioning
confidence: 99%
“…Results shown so far have indicated that P. falciparum parasites, despite having multiple uAUGs/uORFs in the 5 leaders of their mRNAs, are able to translate their CDS by leaky scanning to bypass weak Kozak sequences and by reinitiation at the dORF. Reinitiation has been described previously in P. falciparum for translation of the var2csa gene in the presence of a 360 nucleotide long uORF (Chan et al, 2017), with a parasite translation factor, PTEF, being induced in parasites that are found in the placenta of pregnant women having malaria. Our data show that reinitiation may occur frequently in asexual parasites as well.…”
Section: Assessing the Contribution Of Leaky Scanning And Re-initiatimentioning
confidence: 70%
“…Indeed, a member of the var gene family, the var2csa gene, also has an uORF with a Kozak sequence having 'G' at the +4 position and this uORF plays a role translational repression of the dORF (Chan et al, 2017).…”
Section: The +4 Position Of the Kozak Sequence Plays A Major Role In mentioning
confidence: 99%
“…Experimentally validated uORFs remain unexplored in Toxoplasma and only two examples have been seen in Plasmodium to date, one in the 5′ leader encoded in the var2csa variant of the PfEMP1 gene family and another within gene of unknown function [58,59]. The signal that promotes var2csa protein production remains elusive but its translation involves ribosome reinitiation after uORF translation and is associated with a Plasmodium -specific translation enhancing factor that binds ribosomes, suggesting that changes to the translational machinery permit altered functionality [60,61]. …”
Section: Eif2 Is the Gatekeeper Of The Isr And Latencymentioning
confidence: 99%